2021
DOI: 10.1101/2021.04.20.21255806
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cerebral venous sinus thrombosis (CVST) is not significantly linked to COVID-19 vaccines or non-COVID vaccines in a large multi-state US health system

Abstract: Cerebral venous sinus thrombosis (CVST) has been reported in a small number of individuals who have received the mRNA vaccines1 or the adenoviral vector vaccines for COVID-19 in the US2 and Europe3. Continued pharmacovigilance is integral to mitigating the risk of rare adverse events that clinical trials are underpowered to detect, however, these anecdotal reports have led to the pause or withdrawal of some vaccines in many jurisdictions and exacerbated vaccine hesitancy at a critical moment in the fight again… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…We have also previously shown that the rate of CVST is similar in the 15 and 30 days prior to and after BNT162b2 or mRNA-1273 vaccination in a large cohort at the Mayo Clinic. 26 Taken together with the absence of an increase in emergent clinical visits following each dose, these data suggest favorable tolerability of both vaccines. We show the numbers and percent of individuals in each group who had at least one phenotype-containing EHR note within 7, 14, or 21 days of the actual or assigned first vaccination date.…”
Section: Resultsmentioning
confidence: 82%
“…We have also previously shown that the rate of CVST is similar in the 15 and 30 days prior to and after BNT162b2 or mRNA-1273 vaccination in a large cohort at the Mayo Clinic. 26 Taken together with the absence of an increase in emergent clinical visits following each dose, these data suggest favorable tolerability of both vaccines. We show the numbers and percent of individuals in each group who had at least one phenotype-containing EHR note within 7, 14, or 21 days of the actual or assigned first vaccination date.…”
Section: Resultsmentioning
confidence: 82%
“…We have previously leveraged recent advances in deep neural networks to perform high throughput machine-augmented curation of electronic health record (EHR) systems 5,6 . This has enabled the rapid assessment of real world effectiveness and safety of the mRNA vaccines mRNA-1273 (Moderna) and BNT162b2 (Pfizer/BioNTech), as well as a targeted investigation of cerebral venous sinus thrombosis (CVST) incidence among patients receiving COVID-19 vaccines (including Ad26.COV2.S) within the Mayo Clinic Health System [7][8][9] . We believe such approaches are essential for vaccine development, deployment, and most importantly to build trust and transparency for the public.…”
Section: Introductionmentioning
confidence: 99%
“…Despite previous large-scale studies of similar vaccine efficacy, the number of patients required to find such uncommon post-vaccination events is greater [136]. Data from a large group of US vaccines, in which most were given RNA vaccines, did not find an association with cerebral thrombosis [137]. One of the latter vaccines was temporally associated with a relapse of thrombotic thrombocytopenic purpura in a case report [138].…”
Section: Thrombotic Events and Covid-19 Vaccinationmentioning
confidence: 93%